Supplementary (additional) exploration prospects for the upper viséan gas-condensate pools of Kotelevske field - Міщенко, Л. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2013)
The exploration works are focused on unproved hydrocarbon reserves. There are large parts of the multilayer gas-condensate fields in Ukraine that have numerous small pools in section. Exploration drilling into isolated pools with minor unproved gas reserves is unprofitable. The way out from this situation may be an appraisal-development drilling. Using Kotelevske GCF as an example, it is shown how the areas for appraisal and development drilling in the commercial reserves of hydrocarbons with the possibility of additional exploration of pools with unproved reserves and further transfer of these reserves in the commercial category have been identified by taking into account the geological and geophysical data, evaluation of reservoir rocks properties and analysis of field development.